P297 Left atrial volume index is the best predictor of post-capillary pulmonary hypertension in patients with pure mitral valve stenosis. (17th January 2020) - Santoro, C; Esposito, M; Sorrentino, R; Lembo, M; Esposito, R; Sellitto, V; Luciano, F; Galderisi, M
Abstract: Background: Mitral stenosis (MS) is characterized by a reduced mitral valve area (MVA) and an increased transmitral pressure gradient, with direct consequences on left atrial (LA) remodelling and pulmonary arterial systolic pressure (PASP). Post-capillary pulmonary hypertension (PH) has a main impact on the outcome in patients with MS. Purpose: To evaluate determinants of post-capillary PH in patients with pure MS by using a combined approach of standard and advanced echocardiography. Methods: From January 2018 to January 2019, 52 consecutive patients with MS were enrolled. Concomitant hemodynamically significant valve heart disease, primary PH, coronary artery and congenital heart diseases, primary cardiomyopathies, prosthetic valves and permanent/persistent atrial fibrillation were exclusion criteria. Twenty-three "pure" MS were selected (age: 63.9 ± 11.6 years, F/M= 17/6). Twenty-three healthy controls, matched by age and sex, were recruited as the control group. All participants underwent a complete echocardiographic examination, including determination of left ventricular ejection fraction (LVEF), speckle tracking derived global longitudinal strain (GLS, in absolute values), LA volume index (LAVi) and PASP. MS severity was assessed by continuous wave Doppler derived mean transmitral pressure gradient (MPG), pressure half time (PHT) and functional mitral valve area (MVA). Data were analysed offline by a dedicated workstation. Results: No significant difference of body mass index, systolic and diastolic blood pressure was found between the two groups, while heart rate was higher in MR (p < 0.0001). In the pooled MS population, MPG was 5.7 ± 2.4 mmHg, PHT 127.7 ± 26.9 msec and MVA 1.76 ± 0.36 cm². Twelve patients (52.1%) had mild MS, 10 (43.5%) moderate MS and one (4.3%) severe MS. Patients with MS had larger LA volumes (LAVi = 45.0 ± 12.7 vs. 28.3 ± 7.3 ml/m², p < 0.0001), higher PASP (36.4 ± 8.9 vs. 30.4 ± 6.7 mmHg, p < 0.01), lower LVEF (58.5 ± 6.1 vs. 66.0 ± 3.5%. p < 0.0001) and lower GLS (18.8 ± 4.6 vs. 21.7 ± 2.5%, p < 0.01) than the healthy controls. By analyzing the MS group, LAVi had a significant univariate relation with MPG degree (r = 0.69, p < 0.002). PASP correlated with LAVi (r = 0.60, p = 0.003) and MPG (r = 0.51, p < 0.01) but not with PHT (r = 0.28, p = 0.54) and functional MVA (r=-0.31, p = 0.33). By a multlinear regression analysis, including heart rate, MPG, LVEF and GLS as potential determinants, LAVi (standardized beta coefficient =0.65, p= <0.02) and GLS (beta =-0.62, p = 0.03) were both independently associated with PASP degree, whereas the association of MPG and PASP was not significant (cumulative R²=0.47, SEE = 5.9 mmHg, p < 0.01) in the MS group. Conclusions: In patients with pure MS, by using a multi-parametric echocardiographic approach, LA dilation appears to be the best predictor of post-capillary PH, independent on the magnitude of LV systolic dysfunction and valvular disease severity. Particular care should be devoted to determine LA size in this clinical setting.